Pemindahan Ibu Kota Negara Indonesia dalam Perspektif Hubungan Internasional: Tinjauan Geopolitik dan Potensi Ancaman - Ginanjar, Yusep; Subagyo, Agus (Intermestic: Journal of International Studies, 2024)
This research has the main objective of conducting a strategic review of the relocation of Indonesia's capital city to the East Kalimantan region, where the review focuses on the geopolitical aspects of the archipelago's capital, potential threats arising from the complexity of security in the Indo-Pacific region, and how to develop defense strategies for shape the future of the archipelago's capital city. This research uses the theory of Defensive Realism from Kenneth N. Waltz, as well as the Regional Security Complex Theory from Berry Buzan to show that national security cannot be achieved if a country does not pay attention to regional security. The findings and analysis of the study show that geostrategically the position of the capital of the archipelago is very vulnerable, this is due to its position in the center of the Indo-Pacific region with all the existing security issues. In this condition, air and sea dimensions become the main source of threat considering the development of the conflict between the United States and China, so the development of defense strategy is focused on establishing a layered defense system and improving the air defense system.